An appraisal on the origin of the Veda - Paudel, Ram Chandra (Bodhi: An Interdisciplinary Journal, 2010)
Veda is considered to be the foundational pillar of Vedic philosophical tradition and culture. The emergence of Vedas precedes the recorded history of man. A commonly held view is that they emerged from the innermost core of Brahma's consciousness at the beginning of creation. Various evidences have been put forward to establish that since Veda is one of the most ancient scriptures, it is the means through which humans can achieve worldly success as well as transcend the materialistic existence through realization of Brahman: the ultimate truth. According to the scholars of Vedas, Brahman is a symbol of Sat-Chit- Ananda (Existence-Consciousness-Bliss) and this is the synonym of Vedas. DOI: 10.3126/bodhi.v3i1.2818 Bodhi Vol.3(1) 2009 p.120-124